Editorial on Wireless Power Transfer (WPT): Present Advancements, Applications, and Future Outlooks - Eun S. Lee (Applied Sciences)
The Evolution and Significance of Wireless Power Transfer (WPT): Wireless power transfer (WPT) technologies, which enable the transmission of electrical energy without the need for physical connectors, have emerged as a transformative solution in various industries [...]